La convention d’identité coopérative : création de compromis sectoriels et territoriaux - Amélie Artis; Maryline Filippi; Francesca Petrella (Revue de la Régulation)
While the firm remains a major institution, the cooperative firm remains relatively understudied despite its significant and enduring presence in economic systems. In this article, we highlight the specificity of cooperatives based on a convention of cooperative identity founded on collective ownership and democratic governance. Using case studies, we reveal how the cooperative identity convention and the search for equilibrium caught in sectoral and territorial constraints are expressed. The originality of our contribution lies in the analysis of the cooperative identity convention and the highlighting of adjustments and compromises at the crossroads of sectoral rules and territorial logics. Our conceptualization is in line with the idea of singling out the cooperative enterprise in an institutionalist interpretation.